Penatalaksaan Fisioterapi Pada Kasus Low Back Pain Akibat Spondylosis Lumbalis Di RSUD Dr. Moewardi Surakarta - Puspitaningrum, Gita; , Wahyuni, S.Fis, SKM, M. Kes (2015)
Background : Lower Back pain is one of the health problems that are common in the community. Causes of lower back pain include back pain spondilogenik involving changes in the soft tissues (discs, ligaments and muscles). Lower Back Pain in the case of lumbar spondylosis caused by depletion of the disc and the narrowing of the foramen intervertebrale. Complaints caused from this case is pain, decreased muscle strength, limited range of motion and decreased functional activity. Objective : To know the benefits of modality MWD, TENS, and William Flexion Exercise to reduce pain, increase muscle strength, improve LGS and functional activity. Methods : Physiotherapy methods used in this case with the modality MWD, TENS, and William Flexion Exercise. The evaluation was done by the method of measurement of pain (VDS), LGS measurement (measuring tape), muscle strength (MMT), and functional activity (The Quebec Back Pain Disability Scale). Results : After 6 treatment of therapy showed a decrease in pain relief press T1: mild pain to T6: very mild pain, pain motion T1: pain is not so heavily to T6: mild pain; increase muscle strength, flexor T1: 3 to T6: 4, ekstensor T1: 3 still T6: 3; increase range of motion trunk, flexi T1: 2 to T6: 3, T1 extension: 2 fixed T6: 2; increase in functional activity, T1: 26 scores to T6: 23 scores. Conclusion : In this case the modalities MWD, TENS, and William Flexion Exercise can reduce pain, increase muscle strength, improve LGS, and increase of functional activity